From Ambidexterity to Organizational Agility: The Mediating Role of Strategic Integration in ESG Context - Tegar Ditya Pragama; Disman; Heny Hendrayati; Puspo Dewi Dirgantari; Amirul Afif Muhamat (Jurnal Dinamika Manajemen, 2026)
This study examines the mediating role of Strategic Integration in the relationship between Ambidextrous Capability and both Organizational Agility and Sustainable Value Creation among Indonesian natural resource companies under ESG pressure. Employing PLS-SEM analysis on pooled data of 130 firm-year observations from 65 companies during the 2023-2024 period, data were collected through content analysis of Annual Reports and Sustainability Reports using the Strategic ESG Capability Index with 54 indicators. The findings reveal that Ambidextrous Capability positively affects Strategic Integration, which subsequently influences both Organizational Agility and Sustainable Value Creation. Critically, Strategic Integration fully mediates both the Ambidextrous Capability-Organizational Agility relationship and the Ambidextrous Capability-Sustainable Value Creation relationship, while the non-significant direct effects confirm that Strategic Integration serves as the essential transformation mechanism. Theoretically, this study contributes by addressing the black box problem in ambidexterity-agility literature and operationalizing Dynamic Capabilities Theory into ESG-specific constructs through a validated measurement framework. Practically, the findings provide actionable insights for managers of natural resource companies facing EUDR compliance requirements, demonstrating that ambidextrous capabilities must be channeled through strategic ESG integration to yield agility and sustainable value outcomes.